A dispersion equation of the cylindrical ideal wall vacuum cavity sinusoidally corrugated in azimuthal direction. Part II. Investigation of the dispersion equation - Maksimenko, A.V.; Tkachenko, V.I.; Tkachenko, I.V. (Вопросы атомной науки и техники, 2018)
Dispersion equation of a cylindrical cavity with an ideally conducting outer wall has been investigated, whose
radius is described by a sinusoidal-periodic dependence on the azimuth angle. Numerically and analytically it is
shown that in the neighborhood of intersection points of neighboring harmonics here appear non-transmission bands
in which there are no oscillations of the cavity. The dependence of the width of the unblocking band on the corrugation depth is determined. It is shown that for an arbitrary choice of the corrugation depth and the number of corrugations of the cavity in its frequency spectrum, it is possible that there are no natural frequencies that were originally
assumed to be working. Досліджено дисперсійне рівняння циліндричного резонатора з ідеально провідними стінками, радіус якого описується синусоїдально-періодичною залежністю відносно азимутального кута. Чисельно та аналітично
показано, що поблизу точок перетину сусідніх гармонік з'являються смуги непропускання, в яких коливання
резонатора відсутні. Визначено залежність ширини смуги непропускання від глибини гофрування. Показано, що при довільному виборі глибини гофрування і кількості гофрів резонатора в його частотному спектрі
можлива відсутність тих власних частот, які спочатку передбачалися робочими. Исследовано дисперсионное уравнение цилиндрического резонатора с идеально проводящими стенками,
радиус которого описывается синусоидально-периодической зависимостью относительно азимутального
угла. Численно и аналитически показано, что в окрестности точек пересечения соседних гармоник появляются полосы непропускания, в которых колебания резонатора отсутствуют. Определена зависимость ширины полосы непропускания от глубины гофрировки. Показано, что при произвольном выборе глубины гофрировки и количества гофров резонатора в его частотном спектре возможно отсутствие тех собственных
частот, которые первоначально предполагались рабочими.